2007
DOI: 10.1073/pnas.0702170104
|View full text |Cite
|
Sign up to set email alerts
|

Targeted delivery of proteins across the blood–brain barrier

Abstract: Treatment of many neuronal degenerative disorders will require delivery of a therapeutic protein to neurons or glial cells across the whole CNS. The presence of the blood-brain barrier hampers the delivery of these proteins from the blood, thus necessitating a new method for delivery. Receptors on the blood-brain barrier bind ligands to facilitate their transport to the CNS; therefore, we hypothesized that by targeting these receptors, we may be able to deliver proteins to the CNS for therapy. Here, we report … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
169
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 214 publications
(176 citation statements)
references
References 26 publications
(20 reference statements)
5
169
0
2
Order By: Relevance
“…Routes toward improving the IgV longevity and BBB penetration properties are available (e.g. attachment of an appropriate polypeptide tag) (47)(48)(49).…”
Section: Discussionmentioning
confidence: 99%
“…Routes toward improving the IgV longevity and BBB penetration properties are available (e.g. attachment of an appropriate polypeptide tag) (47)(48)(49).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the transferrin receptor is abundant in brain capillary endothelium, and it has been reported that coupling nanoparticles to transferrin can aid nanoparticle penetration into the BBB through the transferrin receptor mediated pathway. 16,24 Apolipoprotein E is an endogenous protein involved in the trafficking of naturally occurring LDL particles and when grafted on nanoparticles was reported to enhance BBB penetration, [25][26][27][28][29][30] though not necessarily translocation. 9 Similarly, cationised serum albumin has been reported to cross the BBB by absorptive-mediated trancytosis 1,31 and could also be used to gain nanoparticle access to the brain.…”
Section: Introductionmentioning
confidence: 99%
“…Vertebrate BBB cells express lipoprotein receptors, and transcytose both LDL and HDL in tissue culture (Dehouck et al, 1997;Balazs et al, 2004). Furthermore, linking peptides derived from ApoE and ApoB to other molecules can promote their transport across the BBB (Spencer and Verma, 2007;Zensi et al, 2009). However, circulating lipoproteins have never been shown to enter to the brain in vivo.…”
Section: Introductionmentioning
confidence: 99%